2016
DOI: 10.1108/jamr-06-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

The role of coworker and supervisor support on job burnout and job satisfaction

Abstract: Purpose This study investigates the role of coworker and supervisor support on three aspects of burnout (emotional exhaustion, depersonalization, perceived lack of personal accomplishment) and job satisfaction. The authors argue that different sources of social support at work can influence these three aspects of burnout differently. Design/methodology/approach Questionnaires were delivered to supervisors of each campus department at two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
104
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 73 publications
(92 reference statements)
13
104
2
1
Order By: Relevance
“…This is one of the organizational variables that can affect the physical, psychological and spiritual health of individuals, improve their quality of life, and ultimately improve the efficiency of any organization (Esmaeili & Seidzadeh, 2017;Simone, Cicotto, Lampis, 2016). Empirical findings indicate that high job satisfaction is a major determinant of important organizational implications, such as labor market dynamics, employee retention (Pacheco & Webber, 2016), organizational performance improvement (Bacotic, 2016), and productivity (Charoensukmongkol, Moqbel, & Gutiérrez-Wirsching, 2016).…”
Section: Gestión Y Organizaciónmentioning
confidence: 99%
“…This is one of the organizational variables that can affect the physical, psychological and spiritual health of individuals, improve their quality of life, and ultimately improve the efficiency of any organization (Esmaeili & Seidzadeh, 2017;Simone, Cicotto, Lampis, 2016). Empirical findings indicate that high job satisfaction is a major determinant of important organizational implications, such as labor market dynamics, employee retention (Pacheco & Webber, 2016), organizational performance improvement (Bacotic, 2016), and productivity (Charoensukmongkol, Moqbel, & Gutiérrez-Wirsching, 2016).…”
Section: Gestión Y Organizaciónmentioning
confidence: 99%
“…Co-workers are the interactions with each other co-workers including the extent relied on need, help and receptive to work-related problems in the organization (Menguc & Boichuk, 2012). In the survey of two universities in Texas, 174 personnels have taken to show that co-workers support is positive on job satisfaction (Charoensukmongkol, Moqbel, & Gutierrez-Wirsching, 2016). Thus, the following hypotheses:…”
Section: Co-workersmentioning
confidence: 99%
“…Recently, Angeli, Michael, Mustafa and Terk (2015, p. 70) defined burnout as "a state of physical, emotional and mental exhaustion that result from long term involvement in work situations that are emotionally demanding, where the key features lies in the attribution of fatigue and exhaustion to specific domains or spheres in the person's life". An investigation observed the concept burnout as a state of energy depletion and loss of commitment (Peerayuth, Murad, & Sandra, 2016). Though different people can bear different levels of stress for different length of time, burnout most of the times lead a person to become completely nonfunctional.…”
Section: Job Burnoutmentioning
confidence: 99%
“…In a study it was found that job autonomy has a limited negative effect on emotional exhaustion, while a lack of social support will lead to experiencing burnout (Lin, 2013). It is noted that understanding and dealing with employee issues, communicating and providing necessary information by the supervisor and the emotional support in terms of empathy and care from co-workers can significantly help employees alleviate emotional exhaustion and reduce depersonalization (Peerayuth et al, 2016). Therefore, the quality of the social support can affect the level of burnout employees experience at workplace.…”
Section: Role Of Social Support On Job Burnoutmentioning
confidence: 99%